Digital twin paradigm: A systematic literature review - Semeraro, Concetta; Lezoche, Mario; Panetto, Hervé; Dassisti, Michele (Computers in industry, 2021)
•A systematic literature review is conducted to explore the main features, research and technical challenges in conceiving and building Digital Twins.•Topic Modelling Analysis has been implemented to provide an up-to-date picture of the digital twin.•Formal Concept Analysis (FCA) has been applied to understand the digital twin trends and strategies. Manufacturing enterprises are facing the need to align themselves to the new information technologies (IT) and respond to the new challenges of variable market demand. One of the key enablers of this IT revolution toward Smart Manufacturing is the digital twin (DT). It embeds a “virtual” image of the reality constantly synchronized with the real operating scenario to provide sound information (knowledge model) to reality interpretation model to draw sound decisions. The paper aims at providing an up-to date picture of the main DT components, their features and interaction problems. The paper aims at clearly tracing the ongoing research and technical challenges in conceiving and building DTs as well, according to different application domains and related technologies. To this purpose, the main questions answered here are: ‘What is a Digital Twin?’; ‘Where is appropriate to use a Digital Twin?’; ‘When has a Digital Twin to be developed?’; ‘Why should a Digital Twin be used?’; ‘How to design and implement a Digital Twin?’; ‘What are the main challenges of implementing a Digital Twin?’. This study tries to answer to the previous questions funding on a wide systematic literature review of scientific research, tools, and technicalities in different application domains.